102 Peer Teaching in Hip Fracture: Responding to the Medical Needs of Surgical Patients and Educational Needs of Junior Doctors. (4th May 2021) - Jones, N; Francis, J; Parikh, R; Shaath, M
Abstract: Introduction: Fractured Neck of Femur (FNOF) patients are complex. A mortality project identified topics for a peer-led teaching programme. Method: Eight bite-sized case-based sessions were devised, to provide a framework to approach the following topics: Anaemia, delirium/dementia, ECG abnormalities, metastatic cancer, osteoporosis, renal disease, respiratory disease, and vascular complications. Attendees were asked to complete pre- and post- teaching programme questionnaires using a Likert Scale to indicate agreement with statements relating to the topic areas chosen (1=strongly disagree and 5=strongly agree). Result: Pre-programme questionnaire: respondents were neutral (average 3.04) when asked whether topic areas were currently "well managed". Attendees lacked confidence, indicating preparedness as neutral (average 3.35). Trainees agreed that they would benefit from teaching (average 4.56). Post-programme questionnaire: increased confidence was reported when considering preparedness (average 4.3). Attendees felt the teaching programme was "accessible" and the "topics well-chosen". 100% of attendees regarded the teaching as 'excellent' or 'very-good'. Conclusions: Matching patient needs to an educational programme is important. The "bite-sized" nature of the programme paired with case-based learning increased confidence. A peer-led teaching programme is a positive response to themes emerging from morbidity and mortality reviews.